please someone help me
![please someone help me class=](https://us-static.z-dn.net/files/d71/0567bd738b06419f5121f3dea8914a26.png)
Answer:
[tex]( - 12 \div 3) \times ( - 8 + ({ - 4})^{2} - 6) + 2[/tex]
[tex] = ( - 4) \times ( - 8 + 16 - 6) + 2[/tex]
[tex] = ( - 4) \times (2) + 2[/tex]
[tex] = - 8 + 2[/tex]
[tex] = - 6[/tex]
Step-by-step explanation:
[tex]( - 12 \div 3) \times ( - 8 + {( - 4)}^{2} + 2 \\ = - 4 \times ( - 8 + 16 - 6) + 2 \\ = - 4 \times ( - 8 + 10) + 2 \\ = - 4 \times 2 + 2 \\ = - 8 + 2 \\ = - 6 \\ thank \: you[/tex]